VD_FINDINFO HC / 2010 / 119 vom 16. Februar 2010 - VD Tribunal cantonal (2010)
INTERDICTION DE L'ARBITRAIRE, APPRÉCIATION DES PREUVES, MOYEN DE DROIT CANTONAL | 444 al. 1 ch. 3 CPC, 444 al. 1 CPC, 444 al. 2 CPC, 444 CPC, 5 al. 3 CPC, 9 Cst.